Aktifitas Ekstrak Tangkai Daun Coloccasia esculanta Terhadap Staphylococcus aureus - Retno Widyaqori Asyari Putri; Dwi Nur Rikhma Sari; Evi Hanizar (Program Studi Biologi, Fakultas Sains dan Teknologi, UNIPAR JEMBER, 2022)
Taro leaf stems have antibacterial compounds, namely tannins, flavonoids, saponins and alkaloids that have anti-bacterial effects. The purpose of this study was to determine the antibacterial ability of the taro leaf stalk extract using the Staphylococcus aureus test bacteria. This research is an experimental study with samples using pure cultures of S. aureus. The treatments in this study were taro leaf stalk extract concentrations, including 0, 25, 50, 75 and 100 (%) concentrations and used diffusion and dilution methods. The results of the study were analyzed statistically with the Kruskal-Wallis test. The results obtained showed that the diameter of the clear zone of S. aureus at various treatment concentrations was 0% (0 mm); 25% (10.98 mm); 50% (11.93 mm); 75% (13.06 mm); 100% (13.14 mm) with significant results between treatments (5%). For the determination of MIC (Minimum Inhibitory Level) and MBC (Minimum Killing Level) there is a treatment with a concentration of 100%.